Sector Diagnostic and Analysis of Public Spending in Agriculture and Rural Development - World Bank (World Bank, Washington, DC, 2019)
The purpose of this diagnostic report is to establish an analytical basis for defining strategic priorities in agriculture and rural development in Croatia, as the country prepares its National Agriculture and Rural Development Strategy and formulates its Strategic Plan for the European Union’s (EU) Common Agricultural Policy (CAP) for the next programming period (2021-2027). The diagnostic report assesses country-specific strengths, weaknesses, opportunities and threats (challenges) in the context of the macro-trends and issues affecting Croatian agriculture today, the ongoing EU CAP reform process, and broader national development directions. This diagnostic report is based on a series of background documents prepared by the World Bank as key inputs. Both advanced economic analysis and qualitative assessments were carried out as part of an evidence-based process for sector strategy development and policy guidance. Specifically, the analysis focuses on a range of strategic themes related to agriculture and rural development in Croatia, including (i) Croatian agricultural policy and the current CAP; (ii) the efficiency, effectiveness, and equity of current public spending on agriculture and rural development; (iii) the subsidy intensity of income for different farm types, (iv) backward and forward economic linkages of the agriculture and food processing sectors; (v) economy-wide impacts of agriculture and rural development support measures; (vi) agriculture finance and risk management solutions; (vii) the agricultural knowledge and innovation system (AKIS); (viii) food safety, sanitary and phytosanitary (FS&SPS) policies; (ix) trade and strategic market segmentation; (x) agroecological and climate aspects; and (xi) the development of sustainable and circular bio-economies in Croatia. In addition, this report brings forward some key elements of an in-depth sectoral review and policy analysis carried out as an input to the ongoing formulation of Croatia’s broader National Development Strategy (NDS).